Pink salmon fishery in the Far-Eastern fishing basin in 2022: preliminary studies, forecast, interpretation of the fishing season results - E. A. Shevlyakov; A. A. Somov; V. A. Shevlyakov; A. N. Kanzeparova; N. A. Dederer; I. V. Melnikov (Известия ТИНРО, 2023)
Results of marine trawl surveys for accounting of pink salmon in 2021 and 2022 and the main results of the salmon fishery in 2022 are presented. The main stages of forecasting of the pink salmon fishery in the Far Eastern basin are described. Differentiation of mixed aggregations of pink salmon is discussed. In 2022, specialists of Kamchatka Branch used for the first time a new method based on variability of SNP loci, along with the traditional methods (morphological express-method and genetic method based on mtDNA analysis). This method provided additional dividing the mixed aggregations of autumn pink salmon in the Sakhalin-Kuril area to the herds from southern Kuril Islands and from eastern Sakhalin. The fishery forecasts for pink salmon were adjusted several times during the fishing season. These adjustments had no a significant effect for the catch increasing in the Okhotsk Sea basin, but allowed to land 10,500 t additionally in the Bering Sea.